Histopathological features of peripheral T-cell lymphoma in Sprague Dawley rats induced with N-methyl-N-nitrosourea - Al-Salih, Hutheyfa A. H.; Hamzah, Hazilawati; Shaari, Mohd Rosly; Sabri, Jasni; Mohamed Mustapha, Noordin; Sithambaram, Shanmugavelu (Universiti Putra Malaysia Press, 2011)
This study described the histopathological features of peripheral T-cell lymphoma in male Sprague Dawley rats following intraperitoneal (i.p.) injections of N-methyl-N-nitrosourea (MNU) at a dose of 60 mg/kg body weight per injection, administered twice weekly for 2 consecutive weeks, and followed by a five-month’s observation period. Control rats were injected with normal saline, i.p. All the rats treated with MNU had enlargement of lymph nodes, with 30% had hepatosplenomegaly and 7% had enlarged kidneys at necropsy. Malignant lymphoma was observed in the lymph nodes, spleen, liver, lung, heart, and kidneys. The neoplastic cells were characterised as undifferentiated, and small to large size with bizarre pleomorphic nuclei. The severity was further described as mild, moderate and severe, based on the diffuseness of the lesions. Nonetheless, similar lesions were not observed in the thymus of the rats. Immunohistochemistry staining of the organs was positive for CD3 antibody, which is consistent with T-cell lymphoma.